The Effect of Quizizz Media to Teach Students' Writing Skill at MA Al- Mu'tadil - Ach. Zulfi; Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2024)
This research aims to improve students' writing skills. Some students consider writing skills in English to be difficult, boring and unpleasant. Because a teacher's learning model tends to be monotonous and lacking in teaching media. Many students are familiar with smartphones, and some even use them to study. Therefore, by using smartphones teachers and students can access several applications for learning such as quiz applications which have been proven to be effective in learning English. Quizizz is a form of digital instrument that requires all your students to start practicing together in class using technological tools such as computers, iPads, tablets, or smartphones, resulting in fun training for students. This research is a quantitative research using the Pre-Experimental design method using one group pretest-posttest to see the improvement in students' writing skills using media in the form of quizzes. This research was conducted in class XI MIPA MA Al- Mu'tadil. The sample was determined by total sampling technique and the number of samples was 10 people. To assist in data processing and prevent errors in data analysis, researchers used SPSS version 22 to analyze data based on data. From the results of the analysis based on the results of the Paired Sample t Test, the 2- tailed significance value of 0.000 is less than 0.005, indicating a significant difference between the pre-test and post-test with an average value of -38.00000. This shows that there is a significant effect on the difference in the treatment given to each variable.